Factors influencing incident reporting in surgical care. - Kreckler, S; Catchpole, K; McCulloch, P; Handa, A (2009)
OBJECTIVES: To evaluate the process of incident reporting in a surgical setting. In particular: the influence of event outcome on reporting behaviour; staff perception of surgical complications as reportable events. DESIGN: Anonymous web-based questionnaire survey. SETTING: General Surgical Department in a UK teaching hospital. POPULATION: Of 203 eligible staff, 55 (76.4%) doctors and 82 (62.6%) nurses participated. MAIN OUTCOME MEASURES: Knowledge and use of local reporting system; propensity to report incidents which vary by outcome (harm, no harm, harm prevented); propensity to report surgical complications; practical and psychological barriers to reporting. RESULTS: Nurses were significantly more likely to know of the local reporting system and to have recently completed a report than doctors. The level of harm (F(1.8,246) = 254.2, p<0.001), incident type (F(1.9,258) = 64.4, p<0.001) and profession (F(1,135) = 20.7, p<0.001) all significantly affected the likelihood of reporting. Staff were most likely to report an incident when harm occurred. Doctors were significantly less likely to report surgical complications than other types of incident (15% vs 53%, z = 4.633, p<0.001). Fear was a significantly less important barrier to reporting than other reasons (z = -3.49, p<0.0002). CONCLUSION: An incident is more likely to be reported if harm results. Surgical complications are not generally perceived to be "reportable incidents," but they are addressed in Mortality and Morbidity meetings (MandM). Integrating MandM and incident reporting data will result in more comprehensive healthcare safety systems.